Maspin and MCM2 immunoprofiling in salivary gland carcinomas - Helmy Iman M; Ghazy Shaimaa E; Baghdadi Houry M (BMC, 2011)
Abstract Background The pathogenesis of salivary gland carcinomas is very complex and prognostic markers are difficult to find in these carcinomas of which the different subtypes have varying malignant potential. The study was conducted to examine the cellular distribution of maspin and MCM2 in salivary gland carcinomas and their value to predict lymph node metastasis. Materials and methods Fifty three paraffin blocks of different lesions (15 muco-epidermoid carcinoma, 14 adenoid cystic carcinoma, 3 epi-myoepithelial carcinoma, 5 salivary duct carcinoma, 5 malignant pleomorphic adenoma, 6 polymorphous low grade adenocarcinoma and 5 acinic cell carcinoma) were prepared for immunohistochemical staining with maspin and MCM2 antibodies. ANOVA and Pearson correlation tests were used for the statistical analysis of the results. Results All salivary gland carcinomas express maspin and MCM2 with variable cellular localization. There was a significant difference in the expression of each antibody between mucoepidermoid carcinoma, adenoid cystic carcinoma and polymorphous low grade adenocarcinoma. No association was found between examined markers and lymph node metastasis. Conclusions Salivary gland carcinomas express maspin and MCM2 with variable levels and cellular localization, consisting important markers of biological behavior in these tumors. The level of MCM2 expression can be used in the differential diagnosis of adenoid cystic carcinoma and polymorphous low grade adenocarcinoma. Further study with large sample size is recommended to assess their value in prediction of lymph node metastasis.